Hydroacoustic Observations of Two Contrasted Seismic Swarms along the Southwest Indian Ridge in 2018 - Vaibhav Vijay Ingale; Sara Bazin; Jean-Yves Royer (Geosciences, 2021)
In 2018, two earthquake swarms occurred along spreading ridge segments of the ultra-slow Southwest Indian Ridge (SWIR). The first swarm was located at the spreading-ridge intersection with the Novara Fracture Zone, comprising 231 events (ISC catalogue) and spanning over 6 days (10 July to 15 July). The second swarm was more of a cluster of events focusing near a discontinuity, 220 km west of the Rodrigues Triple Junction, composed of 92 events and spanning over 31 days (27 September to 27 October). We examined these two swarms using hydroacoustic records from the OHASISBIO network with seven to nine autonomous hydrophones moored on either side of the SWIR. We detected 1109 hydroacoustic events spanning over 13 days (6 July to 18 July) in the first swarm and 4880 events spanning over 33 days in the second swarm (25 September to 27 October). The number of events per day was larger, and the hydroacoustic magnitude (source level) was, on average, smaller during the second swarm than the first. The spatio-temporal distribution of events from both swarms indicates a magmatic origin initiated by dike intrusions and followed by a readjustment of stresses in the surrounding crust.